Evaluating the effectiveness of treatment of opportunistic vaginal infections in pregnancy - T. E. Karapetyan; V. V. Muravyova; V. L. Tyutyunnik; A. S. Ankirskaya (Медицинский совет, 2013)
The recent progress in clinical microbiology and molecular genetics of microorganisms has greatly expanded our knowledge about the spectrum of opportunistic pathogens. This fact objectively justifies the results of clinical observations on the relationship between opportunistic infections of the vagina and adverse pregnancy outcomes for mother and fetus [1, 7]. However, rational etiotropic treatment of vaginal infections during pregnancy continues to be a challenge. Till present, the question of using antibacterial agents in pregnant women remains controversial [9]. Russian guidelines on the treatment of bacterial vaginosis and Candida vaginitis during pregnancy mainly recommend local therapy, preferably in the II and III trimester. Foreign guidelines focus on systemic effect as early as during the I trimester, while local therapy is optional.